Safe surgery: validation of pre and postoperative checklists - Francine Taporosky Alpendre; Elaine Drehmer de Almeida Cruz; Ana Maria Dyniewicz; Maria de Fátima Mantovani; Ana Elisa Bauer de Camargo e Silva; Gabriela de Souza dos Santos
ABSTRACT Objective: to develop, evaluate and validate a surgical safety checklist for patients in the pre and postoperative periods in surgical hospitalization units. Method: methodological research carried out in a large public teaching hospital in the South of Brazil, with application of the principles of the Safe Surgery Saves Lives Programme of the World Health Organization. The checklist was applied to 16 nurses of 8 surgical units and submitted for validation by a group of eight experts using the Delphi method online. Results: the instrument was validated and it was achieved a mean score ≥1, level of agreement ≥75% and Cronbach's alpha >0.90. The final version included 97 safety indicators organized into six categories: identification, preoperative, immediate postoperative, immediate postoperative, other surgical complications, and hospital discharge. Conclusion: the Surgical Safety Checklist in the Pre and Postoperative periods is another strategy to promote patient safety, as it allows the monitoring of predictive signs and symptoms of surgical complications and the early detection of adverse events.